The Implementation of Muhadhoroh as a Platform for Language Practice in Enhancing Arabic Speaking Skills - Nur Rahmah Lailatul Aulia; Khoiriun Nisa (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2026)
The purpose of this study is to describe and analyze in detail the process of conducting muhadharah, its role in fostering a linguistic environment, and its impact on improving the speaking skills of students at the Al-Humairo Dormitory of the Sunan Drajat Girls’ Islamic Boarding School in Lamongan. This study found that the limited practice of Arabic communication has led to low levels of confidence and fluency in speaking among the students. This study employs a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of these lectures was able to create a participatory, contextual, and adaptive learning environment, thereby gradually improving the students’ confidence, self-assurance, and fluency in speaking, as well as fostering the habit of actively using Arabic in daily life. The novelty of this study lies in the positioning of muhadharah as a structured pedagogical strategy for fostering a language-rich environment, rather than merely an extracurricular activity; thus, this study contributes to environment-based Arabic language learning in Islamic boarding schools.